Differential Muscle Hypertrophy Is Associated with Satellite Cell Numbers and Akt Pathway Activation Following Activin Type IIB Receptor Inhibition in Mtm1 p.R69C Mice - Lawlor, Michael W. (American Society for Investigative Pathology, 2014)
X-linked myotubular myopathy is a congenital myopathy caused by deficiency of myotubularin. Patients often present with severe perinatal weakness, requiring mechanical ventilation to prevent death from respiratory failure. We recently reported that an activin receptor type IIB inhibitor produced hypertrophy of type 2b myofibers and modest increases of strength and life span in the severely myopathic Mtm1δ4 mouse model of X-linked myotubular myopathy. We have now performed a similar study in the less severely symptomatic Mtm1 p.R69C mouse in hopes of finding greater treatment efficacy. Activin receptor type IIB inhibitor treatment of Mtm1 p.R69C animals produced behavioral and histological evidence of hypertrophy in gastrocnemius muscles but not in quadriceps or triceps. The ability of the muscles to respond to activin receptor type IIB inhibitor treatment correlated with treatment-induced increases in satellite cell number and several muscle-specific abnormalities of hypertrophic signaling. Treatment-responsive Mtm1 p.R69C gastrocnemius muscles displayed lower levels of phosphorylated ribosomal protein S6 and higher levels of phosphorylated eukaryotic elongation factor 2 kinase than were observed in Mtm1 p.R69C quadriceps muscle or in muscles from wild-type littermates. Hypertrophy in the Mtm1 p.R69C gastrocnemius muscle was associated with increased levels of phosphorylated ribosomal protein S6. Our findings indicate that muscle-, fiber type-, and mutation-specific factors affect the response to hypertrophic therapies that will be important to assess in future therapeutic trials.